Environmental life cycle assessment of the production in China of lithium-ion batteries with nickel-cobalt-manganese cathodes utilising novel electrode chemistries - Kallitsis,E; Korre,A; Kelsall,G; Kupfersberger,M; Nie,Z (Journal of Cleaner Production, 2020)
Advances in lithium-ion battery (LIB) technology, offering higher mass specific energies, volumetric energy densities, potential differences and energy efficiencies, are key enablers of the large-scale uptake of electric vehicles (EVs). Nickel-cobalt-manganese oxide (NCM) cathode formulations have emerged as the dominant choice in the battery industry. Further performance improvements are expected from the introduction of silicon-graphite composite anodes and nickel-rich cathodes alongside cost reductions achieved through upscaling the battery manufacturing. This work presents results of life cycle assessments concerning the environmental burdens associated with the production of novel electrode batteries and the impacts of the Chinese domination in lithium-ion battery manufacturing. The production of LIBs in China was shown to come at a high environmental cost of 40% higher Global Warming Potential (GWP) than earlier literature suggests. The novel batteries were shown to exhibit similar threats to humans and ecosystems as the commercialised ones, occurring mainly from the metals used in the battery cells; environmental impact reductions are shown to occur as a result of the increased nominal storage capacities of novel battery technologies. The replicable model presented provides the means to quantify the environmental impacts of production of LIBs including those with novel electrode chemistries and offers robust means of decision making that complement scientific and engineering developments targeting LIB performance improvements and cost reductions.